An Integrated Approach to Antisocial Personality Disorder and Bipolar Affective Disorder I - Thasni K C; Asha V; Satheesh K; Vinod R; Aparna P M (AYUSHDHARA, 2025)
Antisocial Personality Disorder (ASPD) is a complex psychiatric condition characterized by impulsivity, aggression, and disregard for others’ rights, affecting approximately 1-4% of the general population. Comorbid Substance use often complicates treatment, with researches indicating 50% of individuals with ASPD also struggles with substance use. The case report shows the scope of integrated approach in personality disorder with comorbid Bipolar Affective Disorder I (BPAD) with substance use combining Ayurvedic interventions, psychological therapy and yoga. A 30-year-old male patient with ASPD and comorbid BPAD I with substance use shows feature of Paithika unmada with Vata anubanda was treated with an integrated approach combining Ayurvedic interventions, cognitive-behavioral therapy, and yoga in an inpatient setting of Govt. Ayurveda Research Institute for Mental Health and Hygiene, Kottakkal. Ayurvedic treatment focused on balancing the predominant Pitta and Vata doshas using medications and procedures such as Virechana, Sirodhara, Rookshana, Snehapana, Vasti, Nasya and Siropichu. Along with these, 4 sessions of cognitive behavioural therapy and daily yoga was given. Assessments were done using Antisocial Personality Disorder Test, Personality Belief Questionnaire (PBQ) and Young’s Mania Rating Scale (YMRS). The patient showed significant improvements in symptoms, including reduced irritability and aggression, decreased substance use, improved sleep quality, and enhanced appetite and overall well-being. This case highlights the potential of Ayurvedic interventions in managing ASPD with comorbid substance use, and demonstrates the effectiveness of an integrated treatment approach.